Kyai Pesantren dan Politik Uang dalam Pilkada Indonesia - Moh. Khoirul Umam; Muchlisin Muchlisin (Resolusi: Jurnal Sosial Politik, 2022)
The article about Kyai pesantren and money politics in the Indonesian elections, aims to explain the position of Kyai in the political configuration of neoliberal democracy, between idealism and pragmatism. This study uses a qualitative method of phenomenological studies. The results of the study explain that the role of Kyai pesantren in the political space of Pilkada has increased over the last few decades or after the political reforms rolled after the collapse of the New Order regime in 1998. In line with the increasing awareness of education and political insight of pesantren. Kyai is often an important element in any political consolidation of Pilkada. It should be noted beforehand that Pilkada is an abbreviation of Regional Head Election. Kyai in Pilkada is like a socio-political instrument that cannot be left behind like magic in politics. Kyai's fatwa and political support have always been a role model for the community. This phenomenon is in line with the paternalistic nature of people's lives and the political culture of the Indonesian people cannot be separated from the socio-political religion. Kyai as candradimuka companions for the people who teach religion and social norms, are unable to patch up the flow of money politics in the neo-liberal democratic system. Every moment of the Pilkada, Kyai becomes a political broker and is trapped in the paragmatism of money politics. The idealism of pesantren which should be a political mission has been defeated by the hegemony of the political ideology of neoliberalism. So that the political mission shifts from the politics of struggle for amar ma'ruf nahi munkar to pragmatism of money politics.